Efficacy of Commiphora myrrh mouthwash on early wound healing after tooth extraction: A randomized controlled trial - Raniah Abdullah Al Eid (Elsevier, 2021)
Background: The early period after tooth extraction is a critical period for wound healing. Wound healing after tooth extraction is considered secondary intention healing. It passes through several stages in the following order: hemostasis, inflammatory phase, proliferative phase, and finally the remodeling phase.Wounds usually heal normally unless there is interference by local or systemic factors. In certain circumstances, early wound healing can be enhanced by several interventions such as antibiotics, mouthwashes, or topical medications. Myrrh has been used as a topical medication for promoting wound healing after tooth extraction. The purpose of this study was to assess the wound healing effect of myrrh mouthwash during the early post-extraction period. Methods: We enrolled 40 healthy adult patients in this study (20: study group and 20: control group). All the activities performed for each group were double-blinded. All the participants underwent dental extraction under local anesthesia using standard protocol. Next, the study group used Commiphora molmol (myrrh) extract as a mouthwash while the control group used normal saline mouthwash. The participants used the mouthwashes twice a day for 7 days starting from the first post-extraction day. Clinical examination data were recorded and analyzed using the Mann Whitney Wilcoxon test. Results: There was a statistically significant between-group difference in postoperative surgical-site edema, tenderness, and socket size, with the test group showing greater improvements. Conclusions: Myrrh mouthwash has an enhancement effect on wound healing during the early period after tooth extraction.